2021
DOI: 10.3390/agronomy11102032
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Begomoviruses from Three Cryptic Species of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) in Nepal

Abstract: The Bemisia tabaci species complex consists of at least 44 cryptic species, which are potential vectors of approximately 320 begomovirus species, most of which are significant plant viruses. However, the relationship of begomovirus transmission through vectors at the cryptic species level is uncertain. In our previous study, three cryptic species (Asia I, Asia II 1, and Asia II 5) of B. tabaci were identified from 76 B. tabaci samples collected across 23 districts in Nepal. Using the same individuals we identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Whiteflies are vectors for at least 320 species of plant viruses belonging to the genera Begomovirus , Carlavirus , Crinivirus , Ipomovirus , Polerovirus and Torradovirus [ 14 , 15 , 16 , 17 ]. Notably, the whitefly species Bemisia tabaci is the sole vector of begomoviruses [ 18 , 19 ] and is considered a complex of at least 44 reproductively isolated but morphologically indistinguishable cryptic species [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whiteflies are vectors for at least 320 species of plant viruses belonging to the genera Begomovirus , Carlavirus , Crinivirus , Ipomovirus , Polerovirus and Torradovirus [ 14 , 15 , 16 , 17 ]. Notably, the whitefly species Bemisia tabaci is the sole vector of begomoviruses [ 18 , 19 ] and is considered a complex of at least 44 reproductively isolated but morphologically indistinguishable cryptic species [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In several Asian countries such as Bangladesh China, Nepal, Thailand, Malaysia and Vietnam, different studies using mtCOI have identified B. tabaci species diversity and their potential as virus vectors [ 17 , 28 , 29 , 30 , 31 , 32 ]. The relevance of characterizing B. tabaci diversity has increased in SEA due to increasing importance of cassava and the recent introduction of CMD in this region [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in Pakistan it has been identified infecting potato (Hameed et al, 2017), soybean (Glycine max L) and cotton (Gossypium hirsutum L.) and in Sri Lanka in bitter gourd, ridge gourd (Luffa acutangular L.), pumpkin and cucumber (Bandaranayake et al, 2014). ToLCNDV was identified in the Seychelles Islands in tomato (Scussel et al, 2018) and more recently in Nepal in three cryptic species of Bemisia tabaci found in Cucurbitaceae and Solanaceae host plants (Acharya et al, 2021), and in China infecting tomato(Figure 6) (Li et al, 2022).…”
Section: Origin and Geographical Distributionmentioning
confidence: 99%